1991
DOI: 10.1203/00006450-199105010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Secretory IgA Receptor on Breast-Milk Macrophages: Evidence for Specific Activation Via These Receptors

Abstract: ABSTRACT. Binding of secretory IgA (sIgA) to human milk macrophages was identified by rosette formation with sIgA-sensitized indicator cells and competitive inhibition binding studies with P 25 I)_sIgA. Macrophages formed rosettes with sIgA-sensitized sheep red blood cells that were inhibited by sIgA (87%) but not IgG. Both IgA) and IgA 2 inhibited sIgA-sensitized sheep red blood cell rosette formation. Rosette formation was completely inhibited by galactose, partially inhibited by asialofetuin, and unaffected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Recently a receptor for Fca (CD89) has been described on the surface of human neutrophils, eosinophils, monocytes and macrophages [27][28][29]. Studies on the molecular nature of the IgA receptor on human phagocytes have shown that it is distinct from the asialoglycoprotein or polymeric IgA receptors [30].…”
Section: Discussionmentioning
confidence: 99%
“…Recently a receptor for Fca (CD89) has been described on the surface of human neutrophils, eosinophils, monocytes and macrophages [27][28][29]. Studies on the molecular nature of the IgA receptor on human phagocytes have shown that it is distinct from the asialoglycoprotein or polymeric IgA receptors [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the majority of BMM express HLA-DR and the intensity of expression on BMM is significantly higher than PBM, simi lar to that described in tissue macrophages The interest in studying FcyR ligand ex pression on BMM was in relation to the role they may have in BMM activity in the nursing infants' GI tract. This is of particular impor tance since there is only indirect evidence of FcaR (receptor for IgA) expression on BMM [29], and recent reports indicate that secretory IgA, abundant in human milk, is an ineffec tive opsonin, and that in fact IgG, which is present in low concentrations (0.05 mg/ml), is responsible for 100% of the BM opsonic activ ity in vitro [30]. [7].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial killing at this pH was~70% that of milk macrophages maintained at pH 7, arguing for the resiliency of the cells at lower gastric pH as the young infant matures and is able to acidify stomach content. The binding of secretory immunoglobulin A (sIgA) to human milk macrophages specifically and the activation of those macrophages via this route has clinical relevance and likely represents a cellular signaling mechanism that enhances the infant's own immune system [151]. Further support of milk macrophage bioactivity comes from in vitro studies in our laboratory where milk macrophages isolated from whole human milk were capable of TGFα and TGFβ 2 secretion [81,152].…”
Section: The Cellular Compartment Of Human Milk: Its Physiologic Relementioning
confidence: 99%